COMPARISON OF BUPIVACAINE VERSUS BUPIVACAINE WITH FENTANYL INTRATHECALLY IN CESAREAN SECTION - PRAJAPATI, JAYSHRI; BAYER, REKHA; PRAJAPATI, HIMANSHU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to evaluate the efficacy and safety of fentanyl with hyperbaric bupivacaine in spinal anesthesia for caesarean section. Methods: This prospective observational study was conducted in anesthesia department of tertiary care teaching hospital of Gujarat. Group A was given 2.0 ml of 0.5% hyperbaric bupivacaine with 0.25 ml of normal saline and Group B received 2.0 ml of 0.5% hyperbaric bupivacaine with 0.25 ml of injection fentanyl (12.5 μg). Characteristics of sensory blockade, motor blockade, analgesia, APGAR score, surgical variables, hemodynamic parameters, and complications were noted and compared in both the groups. Results: There was no significant difference in onset of sensory block in both groups (p>0.05) but there was statistically significant difference present regarding duration of regression of sensory blockade (p<0.05). Time of motor onset and time to get Grade 0 from Grade 3 block were comparable in both groups (p>0.05). Duration of complete analgesia and duration of effective analgesia were significantly prolonged in Group B as compared to Group A (p<0.001). There was also no statistically significant difference observed in mean pulse rate, systolic blood pressure and diastolic blood pressure, and mean arterial pressure in both the groups during entire period of time (p>0.05). Conclusions: The present study concluded that intrathecal fentanyl 12.5 μg with bupivacaine produce prolonged sensory block as well as post-operative analgesia compared to bupivacaine alone for cesarean section with insignificant hemodynamic changes without affecting neonatal outcome.